Estradiol-induced hypophagia is associated with the differential mRNA expression of hypothalamic neuropeptides - Silva,L.E.C.M. (2010)
Estradiol participates in the control of energy homeostasis, as demonstrated by an increase in food intake and in body weight gain after ovariectomy in rats. In the present study, female Wistar rats (200-230 g, N = 5-15 per group), with free access to chow, were individually housed in metabolic cages. We investigated food intake, body weight, plasma leptin levels, measured by specific radioimmunoassay, and the hypothalamic mRNA expression of orexigenic and anorexigenic neuropeptides, determined by real-time PCR, in ovariectomized rats with (OVX+E) and without (OVX) estradiol cypionate treatment (10 µg/kg body weight, sc, for 8 days). Hormonal and mRNA expression were determined at pre-feeding and 4 h after food intake. OVX+E rats showed lower food intake, less body weight gain and lower plasma leptin levels. In the OVX+E group, we also observed a reduction of neuropeptide Y (NPY), agouti-related protein (AgRP) and cocaine- and amphetamine-regulated transcript (CART) mRNA expression in the arcuate nucleus and a decrease in orexin A in the lateral hypothalamic area (LHA). There was an increase in leptin receptor (LepRb), melanocortin-4 receptor (MC4-R), CART, and mainly corticotropin-releasing hormone (CRH) mRNA in the paraventricular nucleus and LepRb and CART mRNA in the LHA. These data show that hypophagia induced by estradiol treatment is associated with reduced hypothalamic expression of orexigenic peptides such as NPY, AgRP and orexin A, and increased expression of the anorexigenic mediators MC4-R, LepRb and CRH. In conclusion, estradiol decreases food intake, and this effect seems to be mediated by peripheral factors such as leptin and the differential mRNA expression of neuropeptides in the hypothalamus.